2004
DOI: 10.1038/sj.npp.1300416
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Anxiety-Like Behavior and Morphine Dependence in CREB-Deficient Mice

Abstract: The transcription factor cAMP-responsive element binding protein (CREB) has been shown to regulate different physiological responses including drug addiction and emotional behavior. Molecular changes including adaptive modifications of the transcription factor CREB are produced during drug dependence in many regions of the brain, including the locus coeruleus (LC), but the molecular mechanisms involving CREB within these regions have remained controversial. To further investigate the involvement of CREB in emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
97
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 47 publications
(81 reference statements)
10
97
4
1
Order By: Relevance
“…We reported earlier that CREB-haplodeficient mice have lower levels of NPY throughout the brain, display higher anxiety-like behaviors, and also have higher preference for alcohol (31). Other investigators have shown that decreased CREB may be involved in anxiety-like behaviors (29,55,56). We also reported earlier that decreased CREB phosphorylation and NPY expression in the CeA might be involved in anxiety-like behaviors during ethanol withdrawal in an unselected stock of rats (30,57).…”
Section: Figuresupporting
confidence: 58%
“…We reported earlier that CREB-haplodeficient mice have lower levels of NPY throughout the brain, display higher anxiety-like behaviors, and also have higher preference for alcohol (31). Other investigators have shown that decreased CREB may be involved in anxiety-like behaviors (29,55,56). We also reported earlier that decreased CREB phosphorylation and NPY expression in the CeA might be involved in anxiety-like behaviors during ethanol withdrawal in an unselected stock of rats (30,57).…”
Section: Figuresupporting
confidence: 58%
“…We propose that CREB, a well known nuclear transcription factor, is the target of nNOS for its roles in modulating anxiety-like behaviors in several paradigms (Valverde et al, 2004). In the present study, 5-HT 1A R agonist promoted CREB phosphorylation, whereas 5-HT 1A R antagonist reduced CREB phosphorylation in vitro and in vivo, suggesting a link between 5-HT 1A R activation and CREB phosphorylation.…”
supporting
confidence: 54%
“…nNOS is required for 5-HT 1A R-mediated CREB phosphorylation CREB knock-out mice exhibited increase in anxiety-like behaviors (Valverde et al, 2004). Neuronal NOS controls CREBmediated gene expression in neurons (Riccio et al, 2006).…”
Section: Nnos Is Required For the Behavioral Effect Of Ssris But Not mentioning
confidence: 99%
“…Moreover, virus-mediated expression of a dominant negative mutant of CREB revealed that local inhibition of CREB activity in the nucleus acccumbens potentiates behavioral responses to emotional stimuli, such as the rewarding effects of drugs of abuse (14,19), but also increases anxiety-like behavior (19). Transgenic mice deficient in CREB expression in the CNS also exhibit an increased-anxiety phenotype (31).…”
mentioning
confidence: 99%